Cytomegalovirus reactivation after hematopoietic stem cell transplant with CMV‐IG prophylaxis: A monocentric retrospective analysis. Issue 11 (19th February 2021) - Gilioli, Andrea; Messerotti, Andrea; Bresciani, Paola; Cuoghi, Angela; Pioli, Valeria; Colasante, Corrado; Bettelli, Francesca; Giusti, Davide; Forghieri, Fabio; Potenza, Leonardo; Donatelli, Francesca; Giubbolini, Rachele; et al.
Abstract: Human cytomegalovirus (CMV) represents the most common viral infection after hematopoietic stem cell transplant (HSCT), mainly occurring as reactivation from latency in seropositive patients, with a different prevalence based on the extent and timing of seroconversion in a specific population. Here, we retrospectively analyzed a cohort of patients who underwent HSCT at our Institution between 2013 and 2018, all of whom were prophylactically treated with CMV‐IG (Megalotect Biotest®), to define the incidence and clinical outcomes of CMV reactivation and clinically significant infection. CMV infection occurred in 69% of our patient series, mainly resulting from reactivation, and CMV clinically significant infection (CS‐CMVi) occurred in 48% of prophylactically treated patients. CMV infection and CS‐CMVi impacted neither on relapse incidence nor on overall survival nor on relapse‐free survival. Moreover, a very low incidence of CMV end‐organ disease was documented. CMV‐IG used alone as prophylactic therapy after HSCT does not effectively prevent CMV reactivation. Highlights: Prophylactic Cytomegalovirus‐specific immunoglobulins alone do not significantly decrease the risk of reactivation after hematopoietic stem cell transplant